Description of two new genera and two new species of antipatharian corals in the family Aphanipathidae (Cnidaria: Anthozoa: Antipatharia) - Opresko, D. M.; Bo, M.; Stein, D. P.; Evankow, A.; Distel, D. L.; Brugler, M. R. (Zootaxa, 2021)
Two new genera and two new species of black corals are recognized in the family Aphanipathidae. The new genus Anozopathes, with the species A. hawaiiensis sp. nov. and A. palauensis, sp. nov. is characterized by a sparsely and irregularly branched corallum with relatively long branches which can be straight, curved or crooked. The genus Aphanostichopathes, with the type species Cirripathes paucispina Brook, is characterized by an unbranched corallum with a long, curved stem with loose distal coils. Mitochondrial DNA data (nad5-IGR-nad1 for Anozopathes and cox3-cox1 for Aphanostichopathes) indicate that both taxa are related to the genera Aphanipathes, Phanopathes and Acanthopathes in the family Aphanipathidae, and morphologically they both share the characteristic of having spines with distinct conical tubercles. The two new species of Anozopathes are separated primarily by differences in colony growth form and in the size and shape of the skeletal spines. Species of Aphanostichopathes are separated primarily by differences in the size and shape of the spines and by size and density of the tubercles on the surface of the spines.